Design of Direct Current Motor Speed Controlled Anchor Based on Root Locus Method. Issue 1 (1st December 2022) - Arunglabi, Rismawaty; Allu, Nicolaus; Merlin
Abstract: The aim of this research is to design the stability of the system by tuning the root locus method for the Direct Current Motor Speed Controlled Anchor. The process is carried out by modeling a DC motor into a mathematical equation so that the transfer function is obtained and then simulated using Matlab with the root locus method. The results of the simulation obtained the value of pole (P1) = -10, pole (P2) = -2, the asymptote intersection point with the real axis τa = − 6 and the break away points of the Root Locus leaving the real axis τb = −6. By looking at the root locus system where the roots of the transfer function are located, all poles are to the left of the imaginary axis and it is stated that the system is stable.